Akhlak Dalam Ajaran Tasawuf Al-Ghazali: Rekonstruksi Tasawuf Akhlaki Dan Relevansinya Bagi Pendidikan Islam Kontemporer - Hakun Mubin; Ita Fauziyah; Tri Astuti Haryati; Amat Zuhri (MGMP PAI SMP BINTAN, 2026)
This article examines the moral dimension (akhlaq) in the Sufism of Abu Hamid al-Ghazali and its relevance to contemporary Islamic education. While al-Ghazali has been widely studied as a theologian, jurist, and mystic, most studies emphasize his epistemology and spirituality, leaving the ethical core of his Sufism underexplored, particularly in character education. This qualitative library research employs content analysis of Ihya’ ‘Ulum al-Din and recent national and international scholarly works. The findings reveal that al-Ghazali’s Sufism is Sunni-oriented, practical (amali), and morally centered (akhlaqi). Akhlaq functions not only as the outcome but also as the method and goal of spiritual discipline through the stages of takhalli, tahalli, and tajalli. This ethical Sufism aligns with the concept of humans as the Divine image, emphasizing moral transformation as the manifestation of spiritual awareness. The study contributes to Islamic education discourse by positioning ethical Sufism as a foundational framework for holistic character education.